Connexin hemichannels and early atrophic signaling in muscle during sepsis - Balboa, Elisa; Saavedra, Fujiko; Cea, Luis A.; Vargas, Aníbal A.; Regueira, Tomás; Sáez, Juan C. (Frontiers in Physiology, 2025)
Sepsis pathogenesis is complex, and effective treatments are limited, leading to high mortality rates between 20% and 55%. Early identification of factors contributing to sepsis-related muscle dysfunction is critical for risk stratification and potential therapeutic development. The immune response during sepsis affects skeletal muscles, contributing to organ dysfunction and worsening prognosis. In this study, we explore the role of connexin hemichannels (Cx HCs) in the early changes in muscle homeostasis during sepsis. Using a cecal ligature and puncture (CLP)-induced sepsis model, we assessed IL-6 levels, weight loss, myofiber cross-sectional area, resting membrane potential, and connexin expression in control and Cx43/Cx45-deficient mice. CLP induced IL-6 elevation, sarcolemma permeabilization, reduced membrane potential, and activation of the ubiquitin–proteasome pathway in control mice, while Cx43/45-deficient mice exhibited reduced all CLP-induced muscle alterations. These findings suggest that Cx43 and Cx45 are involved in the early development of muscle alterations during sepsis.